The Difference Value of Global Pulse Wave Velocity between Type 2 Diabetic and Non-diabetic Patients with Chronic Coronary Syndrome - Fadma Yuliani; Eka Fithra Elfi; Yose Ramda Ilhami; Hirowati Ali (The Indonesian Heart Association, 2026)
Background: Coronary Heart Disease (CHD) remains a major health issue in Indonesia. CHD could lead to myocardial infarction and sudden death, highlighting the necessity for cardiovascular examination and appropriate management to prevent increased morbidity and mortality rates. One non-invasive method for assessing CHD was measuring arterial stiffness using Global Pulse Wave Velocity (PWVg). This study aimed to assess the difference in PWVg among patients with Chronic Coronary Syndrome (CCS) with or without Type 2 Diabetes (T2DM). Methods: This was an analytical cross-sectional study to evaluate the difference in PWVg values among CCS patients with or without T2DM. The study used data from medical records and elective coronary angiography at the Dr. M. Djamil Teaching Hospital’s cardiac catheterization laboratory, where PWVg was measured by Doppler echocardiography examination of CCS patients from April 2023 to 2024. Normality testing using the Shapiro-Wilk test was performed before analyzing all numerical data, followed by independent t-tests or Mann-Whitney tests to determine intergroup differences. Results: The study comprised 36 CCS patients, with 18 samples per group (with and without T2DM). In this study, males were more prevalent in the CCS group without T2DM, smoking risk factors were more commonly found in the CCS group without T2DM, higher Random Blood Glucose (RBG) was found in the CCS group with T2DM, and higher Ankle-Brachial Index (ABI) values were observed in the CCS group without T2DM. Based on statistical analysis, there was a significant difference in PWVg values between the CCS group with T2DM and the group without T2DM (8.3 + 0.7 m/s vs. 7.7 + 0.5 m/s, p=0.009). Conclusion: T2DM results in higher PWVg values compared to those without T2DM among patients with CCS.